Analisa Manajemen Risiko (Kajian Kritis Terhadab Perbankan Syariah di Era Kontemporer) - Mukhlishin, Ahmad; Suhendri, Aan (An-Nisbah: Jurnal Ekonomi Syariah, 2018)
Risk management is an important effort that must be done by every company including Islamic banking, in an effort to minimize losses due to risks that occur. The effort that should be done by Islamic banks in channeling the financing is risk management. Risk management is an effort made by people or institutions in anticipating problems that could arise in a job or business. Risk management in sharia banks has been regulated by Indonesian banks in order to maintain the existence and improve the quality of sharia banks. SWOT strategy that can be done is to strengthen the internal regulation of banks, recruit competent employees, maximum revitalization and tight, build a reliable risk management system, prioritize financing in the sector of SME / SME, do emotional service, improve the ability of FRM, the implementation of office channeling, strengthen the agreement clause.